Effect of 3D printing system and post-curing atmosphere on micro- and nano-wear of additive-manufactured occlusal splint materials. (June 2023) - Wada, Junichiro; Wada, Kanae; Garoushi, Sufyan; Shinya, Akikazu; Wakabayashi, Noriyuki; Iwamoto, Tsutomu; Vallittu, Pekka K.; Lassila, Lippo
Abstract: Although additive manufacturing has been widely applied for occlusal splint (OS) fabrication, it is still unclear whether 3D printing system and post-curing atmosphere would play a role in the wear resistance of additive-manufactured OS. Therefore, the aim of this study was to evaluate the effect of 3D printing system (liquid crystal display (LCD) and digital light processing (DLP)) and post-curing atmosphere (air and nitrogen gas (N2 )) on the wear resistance of hard and soft OS materials for additive-manufactured OSs (KeySplint® Hard and Soft). The evaluated properties were microwear (by two-body wear test) and nano-wear resistances (by nanoindentation wear test) as well as flexural strength and flexural modulus (by three-point bending test), surface microhardness (by Vickers hardness test), and nanoscale elastic modulus (reduced elastic modulus) and nano surface hardness (by nanoindentation test). For the hard material, the surface microhardness, microwear resistance, reduced elastic modulus, nano surface hardness, and nano-wear resistance were significantly affected by the printing system (p < 0.05), while all the evaluated properties except flexural modulus were significantly affected by the post-curing atmosphere ( p  < 0.05). Meanwhile, both the printing system and post-curing atmosphere significantly affected all the evaluated properties ( p  < 0.05). The specimens additive-manufactured by DLP printer tended to show higher wear resistance in the hard material groups and lower wear resistance in the soft material groups when compared to those by LCD printer. The post-curing at N2 atmosphere significantly enhanced the microwear resistance of hard material groups additive-manufactured by the DLP printer ( p  < 0.05) and soft material groups additive-manufactured by the LCD printer ( p  < 0.01), while it significantly enhanced the nano-wear resistance of both hard and soft material groups regardless of the printing system ( p  < 0.01). It can be concluded that 3D printing system and post-curing atmosphere affect the micro- and nano-wear resistance of tested additively manufactured OS materials. In addition, it can be also concluded that the optical printing system providing higher wear resistance depends on the material type, and using nitrogen gas as a protection gas during post-curing enhances the wear resistance of tested materials. Graphical abstract: Image 1 Highlights: Printing system and post-curing affect 3D-printed occlusal splint's wear resistance. The optimal printer providing higher wear resistance depends on the material type. Nitrogen gas atmosphere during post-curing enhances their wear resistance.